KUALITAS FISIK-KIMIA BAKSO DAGING SAPI DENGAN PENAMBAHAN TEPUNG PISANG - Ria Anjalani; Paulini Paulini; Jose Andreano Simangunsong (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aimed to determine the effect of adding banana flour with different levels on the physical-chemical quality of beef meatballs. This study used a Completely Randomized Design with five treatments, namely P0 (beef meatballs with 100% tapioca flour), P1 (beef meatballs with 95% tapioca flour and 5% banana flour), P2 (beef meatballs of 90% tapioca flour and 10% banana flour), P3 (beef meatballs with 85% tapioca flour and 15% banana flour), and P4 (beef meatballs with 80% tapioca flour and 20% banana flour). The study showed no significant differences in beef meatballs' pH, water, protein, and fat content with adding banana flour at different levels (P>0.05). The best results for beef meatballs with banana flour were obtained at 85% tapioca flour and 15% banana flour as fillers.